Cost-benefit analysis of the National Immunization Program in Spain - Alberto Pérez; María Fernández Prada; Natalia Cassinello; Laura Amanda Vallejo-Aparicio; Andrea García; Almudena González; Ana Durán; Néboa Zozaya; Irene Fernández; Mathilde Daheron; Álvaro Hidalgo; Ekkehard Beck; et al. (Taylor & Francis Group, 2024)
Broad benefits of vaccination programs are well acknowledged but difficult to measure, especially when considering all vaccines included in a National Immunization Program (NIP). The aim was to conduct a cost-benefit analysis of the entire NIP in Spain, and an expanded NIP including four potential additional programs. A cost-benefit analysis was performed in Excel to assess the economic and health benefits (€) of vaccinating a single cohort of newborns over a lifetime horizon compared to no vaccination, from a societal perspective: firstly, according to the 2020 NIP in Spain (including 2021 recommendation for herpes zoster in 65-year-olds); and secondly, with an expanded NIP (adding rotavirus and meningococcal B in infants, and pertussis booster in adults aged >65 years and herpes zoster in all adults >50 years). The main inputs were taken from published literature and Spanish databases. Results were presented as a benefit-cost ratio (economic benefit per €1 invested). A cohort of 343,126 newborns were included in the analysis. The total investment needed to vaccinate the cohort throughout their lifetime, according to the 2020 NIP and the expanded NIP, was estimated at €168.5 million and €275.5 million, respectively. Potential economic benefits were €772.2 million and €803.0 million, respectively. The societal benefit-cost ratio was €4.58 and €2.91 per €1 invested, respectively. Even with the addition of new vaccination programs, the Spanish NIP yielded positive benefit-cost ratios from the societal perspective, demonstrating that NIPs spanning the full life course are an efficient public health measure.